Avaliação do comportamento estrutural de alvenarias de terra construídas com blocos de Terra compactados (BTC) - Oliveira, Geilson Marques de (2015)
The purpose of this work is to contribute for an avaliation of the structural behavior of masonry built in blocks of compact soil (BTC). Adopting methods to evaluate the structural behavior, this work focused on determining the way for vertical charges of constructions, taking or not taking into account its interactions with neighbor walls, with or without windows. Were also carried out Tests of resistance to axial compression in BTC blocks and water absorption. Three-point shear strength tests and four-point flexural tensile strength were performed in BTC blocks. The experimental results showed that the crushing of blocks were caused. However, there were no visible fissures in adjacent walls with applied charges.